2018
DOI: 10.1002/cta.2488
|View full text |Cite
|
Sign up to set email alerts
|

One‐cycle controlled quadratic buck converter

Abstract: Summary The quadratic DC‐DC converter can broaden the voltage conversion ratio, which meets the requirements of wide input voltage. However, large‐scale variation of input voltage puts forward harsh requirements on ability to resist input disturbance of control strategy. Quadratic buck converter (QBC) is pulsed nonlinear dynamic systems, so the one‐cycle control strategy based on robustness principle may provide better rejection of power source than the linear feedback control. But the traditional one‐cycle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The technique has been successfully used by the authors in several applications and experiments [1][2][3][4] on converters with different controls including multiphase converters [5][6]. All these studies have been confirmed on clasical converters [7][8][9][10], or new converters [11][12][13][14][15][16], or quadratic converters [17][18][19]. Other high complex approaches investigate the stability analysis of DC-DC converters with DCM (Discontinuous Conduction Mode) operation [20][21][22][23][24] employing a model described by a system of two vector equations: a state equation and another equation that represents a constraint, which is usually non-dynamic.…”
Section: The General and Exact Mathematical Methods For Determining T...mentioning
confidence: 97%
“…The technique has been successfully used by the authors in several applications and experiments [1][2][3][4] on converters with different controls including multiphase converters [5][6]. All these studies have been confirmed on clasical converters [7][8][9][10], or new converters [11][12][13][14][15][16], or quadratic converters [17][18][19]. Other high complex approaches investigate the stability analysis of DC-DC converters with DCM (Discontinuous Conduction Mode) operation [20][21][22][23][24] employing a model described by a system of two vector equations: a state equation and another equation that represents a constraint, which is usually non-dynamic.…”
Section: The General and Exact Mathematical Methods For Determining T...mentioning
confidence: 97%
“…This time, the turn ratio of the coupled inductors appears in the formula of the conversion ratio. A traditional quadratic buck converter (QBC) is presented in [ 26 ], and the traditional one-cycle controlled QBC and an improved version that is obtained by including the inductor current to diode voltage as an integral variable and introducing feedback of output voltage is reported in [ 27 , 28 ]. A series of quadratic step-down DC–DC converters is developed by invoking the principle of reduced redundant power processing.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, quadric boost, 18–22 quadric buck, 23,24 and buck‐boost converters 25–27 reported either use a higher number of passive elements or cannot handle complementary switching. A single switch cascaded boost and buck‐boost converter proposed in Fu et al 28 has a drawback of floating and discontinuous nature of the output.…”
Section: Introductionmentioning
confidence: 99%